Role of Functional Imaging Techniques to Assess Motor and Language Cortical Plasticity in Glioma Patients: A Systematic Review - S. Cirillo; M. Caulo; V. Pieri; A. Falini; A. Castellano (Neural Plasticity)
Cerebral plasticity is the ability of the central nervous system to reorganize itself in response to different injuries. The reshaping of functional areas is a crucial mechanism to compensate for damaged function. It is acknowledged that functional remodeling of cortical areas may occur also in glioma patients. Principal limits of previous investigations on cortical plasticity of motor and language functions included scarce reports of longitudinal evaluations and limited sample sizes. This systematic review is aimed at elucidating cortical brain plasticity for motor and language functions, in adult glioma patients, by means of preoperative and intraoperative mapping techniques. We systematically reviewed the literature for prospective studies, assessing cortical plasticity of motor and language functions in low-grade and high-grade gliomas. Eight longitudinal studies investigated cortical plasticity, evaluated by motor and language task-based functional MRI (fMRI), motor navigated transcranial magnetic stimulation (n-TMS), and intraoperative mapping with cortical direct electrocortical stimulation (DES) of language and motor function. Motor function reorganization appeared relatively limited and mostly characterized by intrahemispheric functional changes, including secondary motor cortices. On the other hand, a high level of functional reshaping was found for language function in DES studies. Occurrence of cortical functional reorganization of language function was described focusing on the intrahemispheric recruitment of perilesional areas. However, the association between these functional patterns and recovery of motor and language deficits still remains partially clear. A number of relevant methodological issues possibly affecting the finding generalization emerged, such as the complexity of plasticity outcome measures and the lack of large longitudinal studies. Future studies are required to further confirm these evidences on cortical plasticity in larger samples, combining both functional imaging and intraoperative mapping techniques in longitudinally evaluations.